El clima organizacional en el desempeño laboral en la Empresa VISPU de la ciudad de Riobamba. - Sinchi Quinche, Blanca Faviola (2023)
In this research work entitled "The organizational climate in labor performance in the VISPU company in the city of Riobamba", the main objective is to demonstrate how the organizational climate influences the performance of the workers of the VISPU company, to identify and improve the negative aspects that support their performance and thus contribute to the overall performance of the company. To carry out this research, the hypothetical-deductive method was developed, and a descriptive research approach was used. The study population consisted of a total of 15 employees of the company, to whom a survey questionnaire was applied to collect the necessary information. Subsequently, the collected data was processed using the Excel tool. The proposed hypothesis was tested by calculating the chi-square value, which turned out to be 15.82, exceeding the critical value of 9.5. Therefore, the null hypothesis is excluded, and the alternative hypothesis is concluded, which establishes that "The organizational climate affects the work performance of VISPU workers in the city of Riobamba". Finally, based on the results obtained in this investigation, conclusions and recommendations are presented that will serve as a guide for the managers of the VISPU company, it is recommended that the VISPU company adopt measures to improve the organizational climate and promote a satisfactory and productive work environment. These measures may include the implementation of training programs and constant updating, as well as guaranteeing compliance with labor rights. It is also suggested to consider the opinions and needs of the workers to improve the infrastructure and the necessary resources. The adoption of these measures can improve the well-being and performance of workers, which in turn will benefit the productivity and profitability of the VISPU company.